ANALISIS BEBAN EMISI UDARA PRIMER DI PROVINSI BANGKA BELITUNG - Elviana Elviana; Arief Sabdo Yuwono; Yudi Chadirin (Jurnal Teknik Sipil dan Lingkungan, 2016)
Economic growth in Bangka Belitung Province is likely to increase. Such improvements have implications on the growing need for fossil fuels from various sectors that cause changes in air quality. Ministry of the Environment recommends doing an inventory of emissions. The load of emissions of sulfur dioxide (SO2), nitrogen oxides (NOx), carbon monoxide (CO), and particulate matter (PM10) is the primary air pollutants dangerous to be inventoried. The average load of SO2 emission Bangka Belitung province of 6,045.89 tons/year and the largest contributor came from the industrial sector (41.43%). Load of NOx emissions by 16,324.84 tons/year, CO amounted to 75,639.01 tons/year, and PM10 amounted to 2,750.66 tons/year. The transportation sector is the largest contributor of load NOx emissions (62.11%), CO (96.58%), and PM10 (79.93%). The largest contributor of load of emissions SO2, NOx, CO, and PM10 in Bangka Belitung is Bangka. Bangka Belitung Provincial Government planned several strategies to reduce the load of emissions include smart driving, energy audit, centralized power plants, and the conversion of kerosene to LPG in the domestic sector. With the implementation of this strategy is expected to reduce load of emissions by 30%.